Assessment of using tunneling and trenchless technology for constricting twin box culvert - Mohammed, Thamer Ahmed; Abdul Kadir, Mohd Razali; Megat Mohd Noor, Megat Johari; Sulaiman, Ahmad Husaini (Universiti Putra Malaysia Press, 2010)
Part of the Seremban flood mitigation project in the state of Negeri Sembilan, Malaysia is to mitigate the flood at Jalan Rasah. The mitigation is planned to be implemented in packages. Package I and Package II of River Anak Air Rasah are parts of the project work. In these packages, wider and deeper concrete sections for the river are constructed. The existing undersized culverts were replaced by bigger reinforced concrete box culverts. The size of the box culverts was based on 100-years average reoccurrence interval (ARI). One of these culverts intersected with a rail line connecting Singapore and Malaysia. Trenchless jacking technique was used to lay the box culvert. The total length of the box culvert jacked under the railway line is 33 m, whereas the total width of the twin box culvert is 7.8 m with a total height of 3 m. This was the first time that the trenchless jacking techniques were used for the urban flood mitigation purpose in Malaysia, and it is mainly used to minimise traffic disruption. This study reports the success of using jacking technique in the development of the flood mitigation program of DID in Negeri Sembilan. Among other things, it explains significant performance of the technique under local conditions and experiences gained towards the advancement of tunnelling and trenchless technology.